(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The microstructure and mechanical properties of high chromium white cast iron with composition: 2,6÷3,4% C; 0,9÷1,1% Si; 0,8÷1,1% Mn; 1,0÷1,3% Mo; 12,3÷13,4% Cr, additionally doped with boron in an amount of 0,18% to 1,25% is investigated. The microstructure of six compositions of white cast irons is studied by means of an optical metallographic analysis - one without boron, and the others contain 0,18%; 0,23%; 0,59%; 0,96% and 1,25% boron. A test is performed to determine: hardness by the Rockwell method; microhardness; bending strength and impact toughness. It was found that at a boron content of 0,18%; 0,23% and 0,59%, the structure of white cast irons is subeutectic, with impact toughness in the range of 1,80÷1,52 J/cm2; with a boron content of 0,96%, the structure of white cast iron is close to the eutectic, with impact toughness 0,98 J/cm2 ; at a boron content of 1,25% the structure of white cast iron is supereutectic and the impact toughness decreases to 0,68 J/cm2. With a change in the boron content from 0,8% to 1,25%, the amount of carbide phase in the structure of white cast iron increases, which leads to an increase in hardness from 53 to 59 HRC. The highest bending strength (Rmi=660,85 MPa) was obtained in white cast irons with a boron content of 0,23%.